Intimacy, Passion and Commitment in Consensual Non-monogamies. An Empirical Study on an International Sample - Paccagnella, Luciano; Enrica Matta; Nicole Braida (Italian Sociological Review, 2024)
The transformations of intimacy represent an important field of study for contemporary sociology. Among these, consensual non-monogamies are forms of relationship in which all partners give explicit consent to engage in romantic, intimate, and/or sexual relationships with multiple people. These new forms of relationship reflect some characteristics of the contemporary world: the flexibility, the reversibility of choices, the redefinition of gender relations, the centrality of open communication among partners. In this study, we applied the well-known Sternberg Triangular Love Scale to measure intimacy, passion and commitment in an international sample consisting of 558 people from 33 countries, who practice forms of consensual non-monogamy and who had at least two simultaneous emotional or romantic relationships at the time of the research. Results seems partially similar to that found in previous studies applying the same scale to monogamous relationships. In particular, it is partially confirmed that the commitment dimension increases with the duration of the relationship, and that the intimacy dimension is substantially stable. Contrary to previous studies that described a progressive waning of passion as the relationship progressed, in our sample this dimension proved to be substantially stable over time. Furthermore, the three dimensions in one relationship are all positively and significantly correlated to the three dimensions in the other relationship. A possible interpretation of this finding is that there is a “virtuous” effect among multiple relationships experienced by the same person: the liveliness, the duration and depth of a relationship do not necessarily subtract resources from the other (or from the others).